KOMPETENSI MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU DI SMP NEGERI 27 MEDAN - Nur Halimah Matondang (Hijri, 2018)
The purpose of this research is to know the 1). The professional competence of teachers, the principal managerial Competencies against professional competence improvement of teacher and principal Strategies in improving the professionalism of teachers in Junior High School 27-country terrain. This type of qualitative research with a naturalistic approach through observation, interviews, and documentation study. Analysis of the data, namely data reduction, data presentation, and conclusion, the validity of the withdrawal of data refers to the four standard validation consists of credibility, keteralihan, dependency, and certainty. The results showed: 1) peneltian. Teacher Professional Competence can be seen from the competence of teachers who teach processed and can be diketahuai that there are teachers who can be said to be professional even though not yet comprehensive. 2). managerial Competence principal against an increase in the professionalism of teachers is done through planning that involves teachers and adapt to the needs of teachers, as well as the implementation of activities that can improve the profesionalsme of teachers and training, 3). The principal strategy in improving the professionalism of teachers through the principal strategies to include and require teachers to follow a training, workshop, following the MGMP (musyawarah guru mata pelajaran, and mastery against the RPP study)Keywords: The Managerial Competencies Of The Principal, Teacher Professionalism